Beyond the immigrant enclave : network change and assimilation - Brown, Susan K. (Sociologist) (New Americans (LFB Scholarly Publishing LLC), 2004)
Immigrant communities - even poor ones - are often portrayed as solidary and supportive. Wierzbicki examines the presence and homogeneity of ties among the foreign- and native-born of different ethnic groups. She finds that the foreign-born consistently report fewer ties than the native-born, in part because of less education or shorter duration of residence. The foreign-born also have more ethnically homogeneous ties, even when they live outside enclaves and in wealthier areas. This finding has implications for theories of assimilation or incorporation. For lack of network data, previous examination of assimilation has often relied on patterns of residential settlement rather than actual social ties. This study indicates that the foreign-born may assimilate spatially but not socially.